Pelepasan Flavonoid Gendarusa vulgaris Nees dari Matriks Sediaan Param Fraksi Etanol 60% dan Param Fasa Air - Astuti, Engrid Juni (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
The aim of the research is to know the different release gendarusin A from the external tradisional dosage form named param 60% ethanol and param water phase. The release gendarusin A was detected using  Transdermal Delivery System equipment and cellophane membrane. Other conditions: Phosphate buffer pH 6,0 as a diffusion Liquid, temperature 37° C ± 0,5° C, sampling time 10, 20, 30, 40, 50, 60 minutes and sample were analysis by HPLC to get concentration of gendarusin A. The result shows that the release flux param at 60% ethanol fraction = 0,6065 µg/cm2/minute1/2 and flux param water phase = 0,3895 µg/cm2/minute1/2.   It means that the release gendarusin A from param ethanol 60% fraction more rapid than param water phase. Release gendarusin A percentage from param 60% ethanol fraction is bigger than param water phase.